ESPECTRO POLÍNICO E INFLUÊNCIA DE PARÂMETROS CLIMÁTICOS NA PRODUÇÃO DE PRÓPOLIS DA ABELHA TUBI - Scaptotrigona aff. postica (Latreille, 1807) (Hymenoptera: Apidae: Meliponini) - SOUZA, Helder Rocha de (2015)
Introduction - There is no specific study on the production of Scaptotrigona aff propolis. postica and the interaction of these bees with vegetation surrounding its colonies. It is known different types of propolis that occur are related to the characteristics fitogeográficas of plant resins that compose them and nothing is known about the correlation climatic factors on production. Given this situation and the increased interest of scientific community to know that propolis is that it proposed to hold this research. Objective - To investigate the influence of abiotic factors in the production of propolis and aspects related to the interactions between bees and the vegetation close to the colonies. Methods - Between April 2011 and March 2012 was collected weekly propolis four colonies of S. aff. postica in Barra do Corda, MA, Brazil. Daily data temperature, rainfall, relative humidity, photoperiod and radiation solar at the trial sites were recorded. We calculated the correlation coefficient Pearson (r) between the mass of the produced propolis and climatic parameters. of each propolis sample pollen grains were extracted and made blades microscopy. The pollen types were identified, counted and relative frequencies obtained. Results - The four hives produced 5,438 annual average g and was 1359.5 ± 80.8 g per hive. The correlation coefficients statistically significant They were: i) rainfall (r = -0.46, p = 0.0039), ii) relative humidity (r = -0.39 P = 0.0156), iii) minimum temperature (r = -0.33, p = 0.0427) and iv) amplitude Thermal (r = 0.32 and p = 0.0494). The correlation between rainfall and humidityRelative air was r = 0.53 and p = 0.0007, and between temperature range and minimum temperature, r = -0.92 And p <0.0001. The analysis of the pollen spectrum, were found 97 types pollen in 35 families. Borreria verticillata (L.) G. Mey. (34.17%) was most frequent species, followed by Anadenanthera sp. (13.65%) and Mimosa caesalpiniifolia Benth. (10.5%). Fabaceae (38.37%) was represented by 30 pollen types while Rubiaceae (34.18%) was represented by only two. There were 28 types exclusive pollen spread between the months of collection. Conclusions - The production of propolis correlates with increasing temperature variation, which occurs due to decreasing the minimum temperature. The increase in rainfall contributes with the decrease in production and the increase in relative humidity and this is positively correlates with production. The interruption in production for three months may be related to diapause queen that may have been triggered by the reduction photoperiod. The wide variety of types of pollen grains found in the samples of Propolis demonstrates strong interaction plant bee and contribute their characterization fitogeográfica. Exclusive pollen types can be used as an indicator for seasonal characterization of propolis.